Menuju Konsep “Maximum Likelihood”: Islam Menjawab Volatilitas Ekspektasi dalam Perekonomian - Ibrahim Kholilul Rozaq; Satria Utama Soekarjono; Nurkholis Nurkholis (Jurnal Iqtisad, 2002)
In terms of the extent of its currency depreciation, many countries in Asia  get serious casualty of this financial crisis. It is paradoxical, given the soundness of Asia’s economic position in 1996 and the economy’s good performance during the first half of 1997, which was supported by tight fiscal policies, prudent monetary policies, and an adequate exchange rate policy. The end result is that the crisis that has afflicted Asia since mid-1997 has radically changed Asia’s economic position, with the exchange rate suffering a severe depreciation of around 30 %-80% percent (for some Asian countries observed) between July 1997 and January 1998. One of the most important things behind the screen of this crisis is a term called: expectation. Expectation has destroyed stability of many variables: Exchange rate, capital flow, the value of debt, trade balance, and inflation that simultaneously break down the stability of economic condition. Expectation based on condition that in Islamic’s perspective: God has cover our heart to think as wise as possible, something non-linear, and –the most dangerous- to act without sense of humanities to other people, or country that suffered by crisis. In more familiar explanation, expectation occured when individual predicts the next condition given by the assumption, value, and rational thinking. Based on this fact, it must be seen that some space has opened to show Islamic view to solve this crisis. With the very limited ability, this study tried to, explore how Islam manage the expectation and give the obligation that this management will converge in economic stability overtime.